2023
DOI: 10.3390/heritage6030168
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Materials and Dyes on Historic Tapestries Using Hyperspectral Imaging

Abstract: Hyperspectral imaging has emerged as a promising analytical method of artwork due to its potential in combining non-invasive analytical capabilities and imaging allowing the survey of the entire (or of a large area of the) surface of an artwork, which is a highly significant application for historic tapestries. This project deployed a high-resolution ClydeHSI Art Scanner, which was used with both a push-broom visible to very-near infrared (VNIR; 400–1000 nm) and near infrared (NIR; 900–1700 nm) hyperspectral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Of the several sets of Acts of the Apostles attributed to the Mattens workshop, no dye analysis has been reported to the knowledge of the authors, except the present study on Miraculous Draught of Fishes at Newfields. This study yielded results from LC-DAD-MS showing that the dyes identified are consistent with known dyestuffs usage in European textiles of the period [32,46,47,51,[55][56][57][58]. Additionally, the newly discovered dye marker pseudoindirubin 1 in a portion of the blue dyed yarns is adduced as a possible objective indication of the simultaneous use of both woad and most likely Asian indigo from India.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Of the several sets of Acts of the Apostles attributed to the Mattens workshop, no dye analysis has been reported to the knowledge of the authors, except the present study on Miraculous Draught of Fishes at Newfields. This study yielded results from LC-DAD-MS showing that the dyes identified are consistent with known dyestuffs usage in European textiles of the period [32,46,47,51,[55][56][57][58]. Additionally, the newly discovered dye marker pseudoindirubin 1 in a portion of the blue dyed yarns is adduced as a possible objective indication of the simultaneous use of both woad and most likely Asian indigo from India.…”
Section: Discussionmentioning
confidence: 78%
“…Though not as prevalent as weld, indigo, and madder, insect dyes are known to have been used in European tapestries in the 16th and 17th centuries [46,51,[55][56][57][58]. If present even in low amounts, the major colorant carminic acid is readily detectable by LC-DAD-MS, and therefore, it is unlikely to have been missed here.…”
Section: Discussionmentioning
confidence: 99%
“…In order to derive a reliable interpretation, data must be compared with those obtained for reference materials [83]. While numerous applications of HSI for the identification of mineral pigments in paintings are available, applications to synthetic organic pigments and dyes remain scarce [83][84][85][86][87], again owing to the limited "fingerprinting" capabilities of the technique towards these materials. Although missing the spectral information, multiband imaging (MBI or MSI), a photographic technique that exploits the absorbance, reflectance and luminescence properties of materials in different ranges of the electromagnetic spectrum, has also been used to map the distribution of synthetic colourants in textiles [78].…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%
“…The examination of three 16th-century tapestries in the Royal Collection, Hampton Court Palace, UK, by means of hyperspectral imaging, described by Constantina Vlachou-Mogire and co-authors, is particularly interesting in this context, as the authors were able to use model samples prepared and dyed as part of the Monitoring of Damage to Historic Tapestries (MODHT) European research project between 2002 and 2005 as standards for comparison. Apart from the preliminary characterisation of the dyes used, the use of false colour images revealed some areas of restoration, while scanning using infrared radiation (VNIR and NIR) of certain areas that appeared to be a uniform colour revealed the use of different dyes [14].…”
Section: Assembly Of Articles In This Special Issuementioning
confidence: 99%